2008
DOI: 10.1063/1.2903524
|View full text |Cite
|
Sign up to set email alerts
|

Influence of structure characteristics on room temperature ferromagnetism of Ni-doped ZnO thin films

Abstract: The influence of structure characteristics on the ferromagnetism of Ni-doped ZnO (ZnO:Ni) thin films prepared by pulsed laser deposition has been investigated by magnetization and resistivity measurements. Structural and optical absorption analyses revealed that Ni has been incorporated into ZnO lattice as Ni2+ substituting for Zn2+ ions and the microstructure of the films becomes more inhomogeneous with increasing Ni content. The room temperature ferromagnetic (FM) behavior only occurs when Ni content is not … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
23
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 69 publications
(24 citation statements)
references
References 20 publications
1
23
0
Order By: Relevance
“…observed room temperature ferromagnetism in ZnO films doped with 1%, 3%, and 5% of Ni [13]. On the other hand, Jin et al found no indication of ferromagnetism in Zn 1-x [16].…”
Section: Introductionmentioning
confidence: 93%
“…observed room temperature ferromagnetism in ZnO films doped with 1%, 3%, and 5% of Ni [13]. On the other hand, Jin et al found no indication of ferromagnetism in Zn 1-x [16].…”
Section: Introductionmentioning
confidence: 93%
“…11,12 However, there are still many inconsistencies and controversies with respect to the origin of the magnetic properties described for Ni-doped ZnO in the literature. For instance, some authors 10,13 observed in their Nidoped ZnO films that the saturation magnetic moments decrease with the Ni-doping concentration. Meanwhile, Thota et al 14 found that the magnetization value of Zn 1−x Ni x O / ZnO ͑0.01Յ x Յ 0.163͒ bilayers increases with an increase in the nickel content.…”
Section: Introductionmentioning
confidence: 99%
“…3. The reduction in the average grain size generates more interface states, which in turn trap the conduction electrons [9,24] and do not allow them to get activated easily in the conduction band as compared to A1 and A2. The same holds for the variation of activation energies calculated in case of thermionic emission of electrons from grain boundary barriers present in all the films.…”
Section: Electrical Conduction Mechanism At Low Temperature Rangementioning
confidence: 98%